Sikap Penerimaan Diri Wanita Infertil di Desa Pandangan Kulon, Kragan, Kabupaten Rembang - Muna, Faizul; Al Khoiron, Muhamad Fiqhussunnah; Putri, Yulita; Nurhuda, Abid (Penerbit Goodwood, 2023)
Purpose: The adolescent The purpose of this study is to describe the attitude of self-acceptance of infertile women in the village of Pandangan Kulon, Kragan, Rembang Regency. Methodology/approach: The method used is qualitative with a field study approach, and then data collection uses observation, interviews, and documentation. Then an interactive analysis was carried out using source and method triangulation techniques. Finally, conclusions are drawn. Results/findings: The results of the study show that the self-acceptance attitude of infertile women goes through several stages, namely denial, anger, depression, bargaining, and acceptance. This is of course a long journey where understanding, sacrifice, and support are needed from various parties such as the husband, extended family, and the community so that new hope emerges because of the strength and willingness to accept the decrees and destiny that Allah SWT has decided for each human being on earth. Conclusions: The attitude of self-acceptance of infertile women goes through several stages, namely denial, anger, depression, bargaining, and acceptance. Limitations: The limitation of this study is that it only limited to two infertile female subjects, it is hoped that further research can obtain more subjects to study. Contribution: This research contributes for everyone, especially women who experience infertility, so it can be a support and reading in life as well as indirect motivation to strengthen them in accepting their predetermined destiny.